2008
DOI: 10.1007/s00213-008-1167-y
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-like behaviors produced by acute fluoxetine administration in male Fischer 344 rats are prevented by prior exercise

Abstract: Rationale-Although selective 5-HT reuptake inhibitors (SSRIs) can reduce anxiety after chronic treatment, acute SSRI administration is associated with an increase in anxiety consistent with an acute increase in 5-HT neurotransmission. Exercise is anxiolytic in humans, and wheel running prevents anxiety-like behavioral consequences of uncontrollable stress in rats, but the effects of exercise on acute fluoxetine-induced anxiety-like behaviors are unknown.Objectives-The current studies tested the hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 77 publications
(116 reference statements)
4
39
0
Order By: Relevance
“…Interestingly, a dose of 2 mg/kg of SB-269970 had no detectable effect in the present study by itself, suggesting a lack of modification of 5-HT release as previously shown (Bonaventure et al, 2007), it counteracted the anxiogenic-like effect of acute administration of fluoxetine in the illuminated open field (Figure 1). Previous reports have shown that the SSRIs fluoxetine and citalopram display anxiogenic behaviors via the activation of 5-HT 2C receptors as their effects were prevented by a 5-HT 2C antagonist (Burghardt et al, 2007;Dekeyne et al, 2000;Greenwood et al, 2008). Hence, it can be suggested that an enhanced activation of 5-HT 2C , and also of 5-HT 7 , receptors might be a mechanism for the anxiogenic effects of SSRIs observed initially during treatment, based on the present results.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, a dose of 2 mg/kg of SB-269970 had no detectable effect in the present study by itself, suggesting a lack of modification of 5-HT release as previously shown (Bonaventure et al, 2007), it counteracted the anxiogenic-like effect of acute administration of fluoxetine in the illuminated open field (Figure 1). Previous reports have shown that the SSRIs fluoxetine and citalopram display anxiogenic behaviors via the activation of 5-HT 2C receptors as their effects were prevented by a 5-HT 2C antagonist (Burghardt et al, 2007;Dekeyne et al, 2000;Greenwood et al, 2008). Hence, it can be suggested that an enhanced activation of 5-HT 2C , and also of 5-HT 7 , receptors might be a mechanism for the anxiogenic effects of SSRIs observed initially during treatment, based on the present results.…”
Section: Discussionsupporting
confidence: 77%
“…Prolonged access to running wheels has been shown to have anxiolytic effects in laboratory rodents (Duman et al 2008;Greenwood et al 2008;Sciolino and Holmes 2012), whereas the effects of acute exercise on anxiety levels are less clear (Youngstedt et al 1993). Thus, in Greenwood's (2009) study, extinction of a context fear memory may not have been affected by running access as rats exposed to chronic exercise were less Cold Spring Harbor Laboratory Press on March 21, 2019 -Published by learnmem.cshlp.org Downloaded from anxious or had lower levels of arousal following extinction training and therefore did not show enhanced extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Though chronic SSRI treatment is anxiolytic, acute SSRI application might be anxiogenic (30). It was also suggested that W-promoting effect of SSRIs might be secondary (81), as SSRI administration was found to cause behavioral and motor activation (9).…”
Section: Discussionmentioning
confidence: 99%